Low-alloy ultra-high-strength steel wire for electric arc additive manufacturing and preparation method thereof

CN117604401BActive Publication Date: 2026-10-13CHINA WEAPON SCI ACADEMY NINGBO BRANCH +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311486740.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-09
Publication Date
2026-10-13
Estimated Expiration
2043-11-09

AI Technical Summary

Technical Problem

[0004]然而,目前超高强钢电弧增材制造技术面临以下问题:(1)电弧增材制造用钢材匮乏,尤其是高强度级别(≥1200MPa)极为缺乏,目前主要采用商用焊丝来替代,在大型构件增材制造过程中容易出现塌陷和裂纹等缺陷,强度塑性较低,难以满足电弧增材制造成形和服役需求;(2)为了获得高强度和高韧性,电弧增材制造用钢材往往需要采用高合金体系,含有大量的Ni、Co等昂贵的合金元素,例如18Ni马氏体时效钢、Ni-Co体系二次硬化超高强钢,在电弧增材制造过程中合金元素会产生严重的枝晶间偏析,使得钢材局部成分偏离设计含量,导致力学性能降低;(3)钢材强度越高,塑性韧性越低,氢脆敏感性增加,尤其当钢材抗拉强度超过1200MPa时,在电弧增材制造过程中容易造成氢致冷裂纹,即使增材构件中氢含量在几个ppm以下,仍会表现出较强的氢脆倾向,降低钢材的强度和塑性以及相应的承载能力和可靠性

Benefits of technology

[0029]与现有技术相比,本发明的优点:本发明的电弧增材制造用低合金超高强钢丝材在合金成分设计中引入多界面强韧化和多相复合强化的设计理念:在电弧增材制造快速凝固冷却条件下形成细小的板条马氏体组织,形成大量的马氏体界面和高密度位错,产生强化作用的同时具有良好的变形能力;利用后续的多次热循环产生回火作用,使得多种纳米碳化物在马氏体高密度位错和界面大量原位析出,产生显著的沉淀强化作用的同时,利用碳化物与基体界面对氢原子的捕获作用,降低氢脆敏感性,从而使得本发明电弧增材制造用低合金超高强钢丝才在表现出高强度的同时具有较高的塑性,改善目前电弧增材制造低合金超高强钢丝材强度塑性低和匹配差的问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004539867080000071
    Figure BDA0004539867080000071
Patent Text Reader

Abstract

The application relates to a low-alloy ultrahigh-strength steel wire for electric arc additive manufacturing and a preparation method thereof. The steel wire is composed of the following components in percentage by mass: C: 0.15-0.30%, Si: 0.3-1.0%, Mn: 0.3-1.0%, Mo: 0.8-2%, Ni: 1-1.5%, Cr: 2-2.5%, V: 0.2-0.9%, Al: <=0.1%, P: <=0.02%, S: <=0.02%, and Fe as the balance. The application guarantees the strength and plasticity through the multi-interface characteristics of the lath martensite matrix, precipitates high-density nanocarbide under the heat treatment effect generated by the multiple thermal cycles of the electric arc additive manufacturing, produces a significant strengthening effect, utilizes the hydrogen capture effect generated by the carbide / matrix interface to reduce the hydrogen embrittlement sensitivity, and thus makes the electric arc additive manufacturing low-alloy ultrahigh-strength steel have higher plasticity while showing high strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of materials technology for arc additive manufacturing, specifically to a low-alloy ultra-high-strength steel wire for arc additive manufacturing and its preparation method. Background Technology

[0002] Ultra-high strength steel is characterized by high strength and good toughness, and is mainly used in energy and chemical industries, marine engineering and shipbuilding, aerospace, weaponry and equipment, mold manufacturing and other fields. With the development of larger equipment and more extreme application environments, higher requirements are placed on the lightweighting and functional-structural integration of complex ultra-high strength steel components. In recent years, the development of additive manufacturing technology has provided new opportunities for the overall manufacturing of large and complex ultra-high strength steel components.

[0003] Among various additive manufacturing methods, arc additive manufacturing technology has the advantages of fast forming speed, high density, and low cost, making it suitable for the rapid overall manufacturing or repair of large, complex, ultra-high-strength steel components. For example, Chinese invention patent application CN202211722219.3 (publication number CN116460391A) discloses "An apparatus and method for manufacturing large martensitic components using arc additive manufacturing." Arc additive manufacturing technology has been successfully applied to the manufacturing and repair of ultra-high-strength steel components such as port machinery hooks, artillery shell bodies, forging dies, and mining sprockets, shortening the component manufacturing cycle, improving material utilization, reducing mold manufacturing processes, and lowering manufacturing costs.

[0004] However, the current ultra-high strength steel arc additive manufacturing technology faces the following problems: (1) There is a shortage of steel for arc additive manufacturing, especially high-strength grade (≥1200MPa). At present, commercial welding wire is mainly used as a substitute. In the process of additive manufacturing of large components, defects such as collapse and cracks are prone to occur. The strength and plasticity are low, which makes it difficult to meet the forming and service requirements of arc additive manufacturing; (2) In order to obtain high strength and high toughness, the steel for arc additive manufacturing often needs to adopt a high alloy system, containing a large amount of expensive alloying elements such as Ni and Co, such as 18Ni martensite. In the process of arc additive manufacturing, the alloying elements of aging steel and Ni-Co system secondary hardening ultra-high strength steel will produce severe interdendritic segregation, causing the local composition of the steel to deviate from the design content, resulting in a decrease in mechanical properties; (3) The higher the strength of the steel, the lower the plasticity and toughness, and the greater the sensitivity to hydrogen embrittlement. Especially when the tensile strength of the steel exceeds 1200MPa, hydrogen-induced cooling cracks are easily caused in the process of arc additive manufacturing. Even if the hydrogen content in the additive component is below a few ppm, it will still show a strong tendency to hydrogen embrittlement, reducing the strength and plasticity of the steel as well as the corresponding load-bearing capacity and reliability.

[0005] Therefore, developing special steels for arc additive manufacturing with low segregation tendency and low hydrogen embrittlement sensitivity is of great significance for the application and promotion of arc additive manufacturing technology in the field of overall rapid steel manufacturing. Summary of the Invention

[0006] The first technical problem to be solved by the present invention is to provide a low-alloy ultra-high-strength steel wire for arc additive manufacturing that has a low segregation tendency and low hydrogen embrittlement sensitivity in the process of arc additive manufacturing, in light of the current state of the prior art.

[0007] The second technical problem to be solved by the present invention is to provide a method for preparing the above-mentioned low alloy ultra-high strength steel wire for arc additive manufacturing, in view of the current state of the prior art.

[0008] The technical solution adopted by the present invention to solve the first technical problem mentioned above is as follows: the low alloy ultra-high strength steel wire for arc additive manufacturing is composed of the following components by mass percentage: C: 0.15-0.30%, Si: 0.3-1.0%, Mn: 0.3-1.0%, Mo: 0.8-2%, Ni: 1-1.5%, Cr: 2-2.5%, V: 0.2-0.9%, Al: ≤0.1%, P: ≤0.02%, S: ≤0.02%, and Fe as the balance.

[0009] The reason why the composition of the low-alloy ultra-high-strength steel wire used in arc additive manufacturing in this invention is controlled within the above range is as follows:

[0010] C: This invention utilizes the heat treatment effect generated by the thermal cycle of arc additive manufacturing to precipitate coherent and semi-coherent nanocarbides with the martensitic matrix during the additive manufacturing process. This produces a significant precipitation strengthening effect, while simultaneously reducing hydrogen embrittlement sensitivity by utilizing the hydrogen atom trapping effect of the carbide-matrix interface. When the carbon content is too low, carbides cannot precipitate or the amount precipitated is insufficient to produce a strengthening effect during arc additive manufacturing. However, when the carbon content is too high, the plastic deformation capacity of the martensitic matrix decreases, cold cracking is easily generated during arc additive manufacturing, and the amount of semi-coherent carbides precipitated with the martensitic matrix increases, leading to a decrease in strength and plasticity, and an increase in hydrogen embrittlement sensitivity. Therefore, the carbon content is controlled at 0.15-0.30%.

[0011] Si and Mn: Si and Mn have a combined deoxidizing effect in arc additive manufacturing, forming silicates with low density and low melting point, which easily float out of the molten pool and are less likely to cause inclusions in continuous additive manufacturing. However, excessive Si and Mn content increases the number of inclusions during steel manufacturing, reducing strength and toughness. Therefore, in this invention, the Si content is controlled at 0.3-1.0%, and the Mn content is controlled at 0.3-1.0%.

[0012] Mo: This invention utilizes the heat treatment effect of Mo in the arc additive manufacturing thermal cycle to precipitate semi-coherent carbides with carbon, thereby producing precipitation strengthening while mitigating the detrimental effects of coherent carbides on plasticity. Furthermore, Mo can achieve supersaturated solid solution in the martensitic matrix during the rapid cooling process of arc additive manufacturing, resulting in solid solution strengthening. When the Mo content is too low, the aforementioned precipitation strengthening and solid solution strengthening effects are difficult to achieve. However, when the Mo content is too high, it leads to coarsening of the semi-coherent carbides with the martensitic matrix during arc additive manufacturing, while simultaneously reducing the plastic deformation capacity of the martensitic matrix, resulting in a decrease in the strength and toughness of the steel wire used in arc additive manufacturing. Therefore, the Mo content in this invention is controlled at 0.5-2.0%.

[0013] Ni: Ni can increase the ductility and toughness of steel used in arc additive manufacturing, but excessive Ni content increases the cost of the steel, increases the segregation of elements between dendrites during arc additive manufacturing, and may even cause retained austenite, reducing the strength and ductility of the steel wire used in arc additive manufacturing. Therefore, the Ni content in this invention is controlled at 1-1.5%.

[0014] Cr: In this invention, Cr precipitates under the heat treatment effect of the arc additive manufacturing thermal cycle, forming semi-coherent carbides with C and Mo. This precipitation strengthening effect mitigates the detrimental effects of coherent carbides on plasticity. Furthermore, Cr is a ferrite (martensite) stabilizing element, and Ni, added in this invention to improve plasticity and toughness, is an austenitizing stabilizing element. Therefore, another function of adding Cr is to ensure that the steel has a fully martensitic structure after cooling in arc additive manufacturing. However, excessive Cr content can cause high-temperature ferrite formation and lead to coarsening of semi-coherent carbides, reducing plasticity and toughness. In this invention, the Cr content is controlled at 2-2.5%.

[0015] Vanadium carbide (V) in this invention forms coherent nano-carbides with carbon under the heat treatment effect of the arc additive manufacturing thermal cycle. This produces a significant precipitation strengthening effect without compromising ductility and toughness. Furthermore, the interface between vanadium carbide and the martensitic matrix traps hydrogen atoms, reducing hydrogen embrittlement sensitivity. However, excessive V content can lead to severe interdendritic segregation during arc additive manufacturing, resulting in reduced strength and ductility. Therefore, the Ni content in this invention is controlled at 0.2-0.9%.

[0016] Al: Al has a deoxidizing effect, but similar to Si, the oxides it forms have high melting points, which can easily cause inclusions during additive manufacturing. Excessive aluminum content can increase spattering in high-strength steel wire during additive manufacturing and increase the tendency for hot cracking. Therefore, in this invention, Al is used as an impurity element, and its content is controlled to be below 0.1%.

[0017] Preferably, the low-alloy ultra-high strength steel wire used in arc additive manufacturing has a tensile strength ≥1300MPa, a yield strength ≥1000MPa, and an elongation after fracture ≥12% when the deposited metal has been subjected to heat treatment without hydrogen removal.

[0018] The technical solution adopted by the present invention to solve the second technical problem mentioned above is: a method for preparing the above-mentioned low-alloy ultra-high-strength steel wire for arc additive manufacturing, characterized in that it includes the following processing steps:

[0019] (1) Alloy smelting: The steel ingot is initially smelted under vacuum conditions, and the initially smelted ingot is forged into electrodes. The electroslag remelting method is then used for secondary smelting to obtain a secondary smelted ingot; (controlling the content of impurity elements such as P and S);

[0020] (2) High-temperature forging: The secondary smelting ingot is forged at high temperature to obtain bar stock;

[0021] (3) High-temperature rolling: The bar stock is rolled at high temperature to obtain wire rod;

[0022] (4) Softening annealing treatment: The wire rod obtained by rolling is subjected to softening annealing treatment;

[0023] (5) Drawing: The softened wire rod is drawn to obtain the steel for arc additive manufacturing.

[0024] Preferably, in step (1), the vacuum degree of vacuum smelting is 13-18 Pa, and the specific parameters of the initial melting and forging of the electrode are: the ingot is held at 1050-1100℃ for a set time to reduce ingot segregation, and the final forging temperature of the forged electrode sample is not lower than 900℃; the specific parameters of the electroslag remelting process are: electroslag speed 1.4-1.8 kg / min, voltage 26-30V, current 1.6-2.0kA.

[0025] Preferably, in step (2), the specific process of high-temperature forging is as follows: the ingot is held at 1000-1050℃ for a set time, forged into a bar shape, and the final forging temperature is not lower than 900℃, followed by air cooling.

[0026] Preferably, in step (3), the specific process of high-temperature rolling is as follows: the forged bar is kept at 1000-1050℃ for a set time, rolled into wire rod in multiple passes, and then air-cooled.

[0027] Preferably, in step (4), the specific parameters of the softening annealing treatment are: the wire rod is kept in a salt bath at 950℃-1050℃ for a set time so that the hardness of the wire rod is reduced, followed by air cooling.

[0028] Preferably, in step (5), the specific process of drawing is as follows: removing the oxide scale on the surface of the wire rod, washing and drying it with water, performing a film treatment, drying it, and then drawing it. During the drawing process, online annealing is carried out at 950-1000℃, followed by alkali washing and water washing.

[0029] Compared with existing technologies, the advantages of this invention are as follows: The low-alloy ultra-high-strength steel wire for arc additive manufacturing of this invention introduces the design concepts of multi-interface toughening and multi-phase composite strengthening in the alloy composition design: Under the rapid solidification and cooling conditions of arc additive manufacturing, fine lath martensite structure is formed, resulting in a large number of martensite interfaces and high-density dislocations, which produce a strengthening effect while maintaining good deformability; the subsequent multiple thermal cycles generate a tempering effect, causing a large number of nano-carbides to precipitate in situ at the high-density dislocations and interfaces of the martensite, producing a significant precipitation strengthening effect. At the same time, the hydrogen embrittlement sensitivity is reduced by utilizing the hydrogen atom capture effect of the carbide-matrix interface. Thus, the low-alloy ultra-high-strength steel wire for arc additive manufacturing of this invention exhibits both high strength and high plasticity, improving the problems of low strength and poor plasticity matching in current low-alloy ultra-high-strength steel wires for arc additive manufacturing.

[0030] In other words, this invention ensures strength and plasticity through the multi-interface characteristics of the lath martensitic matrix. The heat treatment effect generated by multiple thermal cycles in arc additive manufacturing precipitates high-density nano-carbides, which produces a significant strengthening effect. At the same time, the hydrogen capture effect generated by the carbide / matrix interface reduces the hydrogen embrittlement sensitivity of high-strength low-alloy steel wire manufactured by arc additive manufacturing. Thus, low-alloy ultra-high-strength steel manufactured by arc additive manufacturing exhibits high strength and high plasticity.

[0031] The steel wire of this invention, while ensuring the formability of arc additive manufacturing, selects alloying elements such as Cr and Mo that have a low tendency to segregate during solidification, and controls the content of alloying elements. This significantly reduces the segregation tendency in arc additive manufacturing while reducing the material cost of the steel.

[0032] In addition, the steel of this invention has a stable manufacturing process, good additive manufacturing formability, and low hydrogen embrittlement sensitivity. It is suitable for arc additive manufacturing of high-strength steel components, especially for arc additive manufacturing of low alloy ultra-high strength steel parts with tensile strength requirements of 1300MPa or higher. Detailed Implementation

[0033] The present invention will be further described in detail below with reference to specific embodiments.

[0034] Example 1

[0035] The method for preparing low-alloy ultra-high-strength steel wire for arc additive manufacturing in this embodiment includes the following steps:

[0036] (1) Alloy smelting: The steel ingot is smelted under vacuum conditions, the smelted ingot is forged into an electrode, and then the electroslag remelting method is used for secondary smelting to obtain the secondary smelted ingot.

[0037] Specifically, the initial smelting process involves using a vacuum furnace to smelt the steel ingots at a vacuum level of 15 Pa. The ingots are then held at 1050℃ for 4 hours to reduce segregation. Finally, the ingots are forged into Φ80 electrode samples, with a final forging temperature of no less than 900℃.

[0038] The secondary smelting was carried out using the electroslag remelting method, with an electroslag speed of 1.6 kg / min, a voltage of 28 V, and a current of 1.8 kA.

[0039] (2) High-temperature forging: The secondary smelting ingot is forged at high temperature to obtain bar stock; specifically: the ingot is held at 1000℃ for 2 hours and forged into a 50mm×50mm square bar with a final forging temperature of not less than 900℃ and air-cooled.

[0040] (3) High temperature rolling: The bar stock is rolled at high temperature to obtain wire rod; specifically: the forged square bar is held at 1000℃ for 2 hours and rolled into Φ6.5 wire rod in multiple passes, and then air-cooled.

[0041] (4) Softening annealing treatment: The rolled wire rod is subjected to softening annealing treatment; specifically, the wire rod is kept in a 980℃ salt bath for 1 hour to reduce the strength of the wire rod, and then air-cooled.

[0042] (5) Drawing: The softened wire rod is drawn to obtain the steel wire for arc additive manufacturing. Specifically, the oxide scale on the surface of the wire rod is removed by turning or other machining methods. After washing and drying, a film treatment is performed. After drying at 80°C, the wire rod is drawn. The drawing diameter changes as follows: Φ6.1→Φ5.5→Φ5.0→Φ4.4→Φ4.0→online annealing + sodium hydroxide solution alkaline washing + water washing→Φ3.5→Φ2.8→online annealing + sodium hydroxide solution alkaline washing + water washing→Φ2.2→Φ1.97→Φ1.76→Φ1.58→Φ1.43→Φ1.3→Φ1.2. The wire rod is then washed, dried at 80°C, and wound into a coil to produce the low alloy ultra-high strength steel wire for arc additive manufacturing.

[0043] The performance of the steel wire for arc additive manufacturing prepared in this embodiment was tested:

[0044] Arc additive manufacturing specimens were prepared using a Fronius CMT welding power source and an ABB robot. The substrate was a 20mm thick low-alloy ultra-high-strength steel plate. The wire feed speed was 7m / min, argon was used as the shielding gas at a flow rate of 20L / min, the welding torch scanning speed was 6mm / s, and the interlayer dwell time during arc additive manufacturing was 60s. No heat treatment was performed after additive manufacturing. Tensile specimens were cut along the length of the welding torch. M10 standard tensile specimens were used to measure tensile strength, yield strength, and elongation after fracture.

[0045] Example 2

[0046] The preparation method of low-alloy ultra-high-strength steel wire for arc additive manufacturing in this embodiment includes the following processing steps:

[0047] (1) Alloy smelting: The steel ingot is smelted under vacuum conditions, the smelted ingot is forged into an electrode, and then smelted again by electroslag remelting to obtain a smelted ingot.

[0048] Specifically, the initial smelting process involves using a vacuum furnace to smelt low-alloy ultra-high-strength steel wire alloy at a vacuum level of 15 Pa. The ingot is then held at 1070℃ for 4 hours to reduce ingot segregation. The ingot is then forged into Φ80 electrode samples, with a final forging temperature of no less than 900℃.

[0049] The secondary smelting was carried out using the electroslag remelting method, with an electroslag speed of 1.6 kg / min, a voltage of 28 V, and a current of 1.8 kA.

[0050] (2) High-temperature forging: The secondary smelting ingot is forged at high temperature to obtain bar stock; specifically: the ingot is held at 1000℃ for 2 hours and forged into a 50mm×50mm square bar with a final forging temperature of not less than 900℃ and air-cooled.

[0051] (3) High temperature rolling: The bar stock is rolled at high temperature to obtain wire rod; specifically, the forged square bar is held at 1050℃ for 2 hours and rolled into Φ6.5 wire rod in multiple passes, and then air-cooled.

[0052] (4) Softening annealing treatment: The rolled wire rod is subjected to softening annealing treatment; specifically, the wire rod is kept in a salt bath at 1020℃ for 1 hour to reduce the strength of the wire rod, and then air-cooled.

[0053] (5) Drawing: The softened wire rod is drawn to obtain the steel for arc additive manufacturing.

[0054] Specifically, the wire rod is kept in a 1020℃ salt bath for 1 hour and then air-cooled. The oxide scale on the surface of the wire rod is removed by turning or other machining methods. After washing and drying, a film treatment is performed. After drying at 80℃, it is drawn, with the drawing diameter changing as follows: Φ6.1→Φ5.5→Φ5.0→Φ4.4→Φ4.0→online annealing + sodium hydroxide solution alkaline washing + water washing→Φ3.5→Φ2.8→online annealing + sodium hydroxide solution alkaline washing + water washing→Φ2.2→Φ1.97→Φ1.76→Φ1.58→Φ1.43→Φ1.3→Φ1.2. After washing, it is dried at 85℃, wound into a coil, and thus produced the low-alloy ultra-high-strength steel wire for arc additive manufacturing.

[0055] The performance of the steel for arc additive manufacturing prepared in this embodiment was tested:

[0056] Arc additive manufacturing samples were prepared using a Fronius CMT welding power source and an ABB robot. The substrate was a 20mm thick low-alloy ultra-high-strength steel plate. The wire feed speed was 7.5m / min, argon was used as the shielding gas at a flow rate of 20L / min, the welding torch scanning speed was 6.5mm / s, and the interlayer dwell time during arc additive manufacturing was 80s. No heat treatment was performed after additive manufacturing. Tensile specimens were cut along the length of the welding torch. M10 standard tensile specimens were used to measure tensile strength, yield strength, and elongation after fracture.

[0057] Example 3

[0058] The preparation method of low-alloy ultra-high-strength steel wire for arc additive manufacturing in this embodiment includes the following processing steps:

[0059] (1) Alloy smelting: The steel ingot is smelted under vacuum conditions, the smelted ingot is forged into an electrode, and then smelted again by electroslag remelting to obtain a smelted ingot.

[0060] Specifically, the low-alloy ultra-high-strength steel wire alloy was initially melted in a vacuum furnace at a vacuum level of 15 Pa. The ingot was held at 1100℃ for 4 hours to reduce segregation. It was then forged into Φ80 electrode samples, with a final forging temperature of not less than 900℃. A secondary melting process was then performed using electroslag remelting at a rate of 1.6 kg / min, a voltage of 28 V, and a current of 1.8 kA.

[0061] (2) High-temperature forging: The secondary smelting ingot is forged at high temperature to obtain bar stock; specifically: the ingot is held at 1030℃ for 2 hours and forged into a 50mm×50mm square bar with a final forging temperature of not less than 900℃ and air-cooled.

[0062] (3) High temperature rolling: The bar stock is rolled at high temperature to obtain wire rod; specifically, the forged square bar is held at 1050℃ for 2 hours and rolled into Φ6.5 wire rod in multiple passes, and then air-cooled.

[0063] (4) Softening annealing treatment: The rolled wire rod is subjected to softening annealing treatment; specifically, the wire rod is kept in a salt bath at 1050℃ for 1 hour to reduce the strength of the wire rod, and then air-cooled.

[0064] (5) Drawing: The softened wire rod is drawn to obtain the steel wire for arc additive manufacturing.

[0065] Specifically, the oxide scale on the surface of the wire rod is removed by turning or other machining methods. After washing and drying, a film treatment is performed. After drying at 80℃, the wire rod is drawn, with the drawing diameter changing as follows: Φ6.1→Φ5.5→Φ5.0→Φ4.4→Φ4.0→online annealing + sodium hydroxide solution alkaline washing + water washing→Φ3.5→Φ2.8→online annealing + sodium hydroxide solution alkaline washing + water washing→Φ2.2→Φ1.97→Φ1.76→Φ1.58→Φ1.43→Φ1.3→Φ1.2. After washing, the wire rod is dried at 100℃ and wound into a coil to produce the low alloy ultra-high strength steel wire for arc additive manufacturing.

[0066] The performance of the steel for arc additive manufacturing prepared in this embodiment was tested:

[0067] Arc additive manufacturing specimens were prepared using a Fronius CMT welding power source and an ABB robot. The substrate was a 20mm thick low-alloy ultra-high-strength steel plate. The wire feed speed was 8m / min, argon was used as the shielding gas at a flow rate of 20L / min, the welding torch scanning speed was 7mm / s, and the interlayer dwell time during arc additive manufacturing was 90s. No heat treatment was performed after additive manufacturing. Tensile specimens were cut along the length of the welding torch. M10 standard tensile specimens were used to measure tensile strength, yield strength, and elongation after fracture.

[0068] Comparative Example 1

[0069] 18Ni-11Co martensitic aging steel wire was used as a comparative example. The wire composition is shown in Table 1, with an alloy element content exceeding 30%. The wire diameter was Φ1.2mm. Arc additive manufacturing forming experiments were conducted using a Fonnius CMT welding power source. The substrate was made of low-alloy ultra-high-strength steel with a thickness of 20mm. Argon was used as the shielding gas, with a wire feed speed of 7.5m / min (unified control of welding process parameters), a welding torch scanning speed of 5mm / s, and a gas flow rate of 25L / min. The mechanical properties were tested in both the stacked state and the hydrogen-free heat treatment state (200℃ for 12h, air cooling). Tensile specimens were cut along the length of the welding torch. The specimen specifications were M10 standard tensile specimens, and tensile performance tests were performed. The mechanical properties are shown in Table 2.

[0070] Table 1. Chemical composition of the ultra-high strength steel wires produced in the examples and comparative examples.

[0071] Example 1 0.18 0.40 0.60 0.90 1.00 2.30 0.41 -- -- 0.05 Example 2 0.24 0.40 0.45 1.10 1.10 2.37 0.60 -- -- 0.07 Example 3 0.27 0.42 0.41 1.40 1.08 2.43 0.72 -- -- 0.04 Comparative Example 1 0.005 0.05 -- 3.96 17.13 -- 11.02 1.64 0.18

[0072] Table 2. Room temperature mechanical properties of arc additive manufacturing deposited metal (accumulated state) of ultra-high strength steel wire in the examples and comparative examples.

[0073]

[0074] The wire alloy composition of the above embodiments contains P and S impurities, P: ≤0.02%, S: ≤0.02%, and the balance is Fe.

[0075] The steel wire prepared by this invention has a low alloying element content, not exceeding 7%. It exhibits low segregation tendency, low hydrogen embrittlement sensitivity, and good additive formability during arc additive manufacturing. Under non-heat treatment conditions, its tensile strength can reach over 1300 MPa, its yield strength over 1000 MPa, and its elongation after fracture is not less than 12%.

[0076] The ultra-high strength martensitic aging steel wire of the 18Ni-11Co system used in Comparative Example 1 has an alloy element content of over 30%, and its cost is much higher than that of the steel of the present invention. It has a strong hydrogen embrittlement sensitivity during the arc additive manufacturing process. Without heat treatment, the weld metal of the arc additive manufacturing is prone to brittle fracture in the elastic stage when stretched at room temperature, with a tensile strength of only 620 MPa and an elongation after fracture of only 2%. It requires long-term hydrogen removal heat treatment (holding at 200°C for more than 12 hours) to obtain the strength and elongation after fracture comparable to that of the present invention, which increases energy consumption and time costs and is not conducive to the overall rapid prototyping of large and complex components by arc additive manufacturing.

Claims

1. A low-alloy ultra-high-strength steel wire for arc additive manufacturing, characterized in that: The steel wire is composed of the following components by mass percentage: C: 0.15-0.30%, Si: 0.3-1.0%, Mn: 0.3-1.0%, Mo: 0.8-2%, Ni: 1-1.5%, Cr: 2-2.5%, V: 0.6-0.9%, Al: ≤0.1%, P: ≤0.02%, S: ≤0.02%, and Fe as the balance. This steel wire is manufactured using arc additive manufacturing. Under the rapid solidification and cooling conditions of arc additive manufacturing, a fine lath martensite structure is formed, resulting in numerous martensite interfaces and high-density dislocations. This produces a strengthening effect while maintaining good deformability. Subsequent multiple thermal cycles generate a tempering effect, causing various nano-carbides to precipitate in situ at the high-density dislocations and interfaces of the martensite. This produces a significant precipitation strengthening effect, while the hydrogen embrittlement sensitivity is reduced by utilizing the hydrogen atom trapping effect of the carbides at the matrix interface. This steel wire, when used in arc additive manufacturing, provides a tensile strength ≥1300MPa, a yield strength ≥1000MPa, and an elongation after fracture ≥12% for the deposited metal under conditions of no hydrogen removal heat treatment. The steel wire can precipitate high-density nano-carbide under the heat treatment effect of multiple thermal cycles in electric arc additive manufacturing.

2. A method for preparing the low-alloy ultra-high-strength steel wire for arc additive manufacturing as described in claim 1, characterized in that, The processing steps include the following: (1) Alloy smelting: The steel ingot is smelted under vacuum conditions, the ingot is forged into an electrode, and then smelted again by electroslag remelting to obtain a smelted ingot. (2) High-temperature forging: The secondary smelting ingot is forged at high temperature to obtain bar stock; (3) High-temperature rolling: The bar stock is rolled at high temperature to obtain wire rod; (4) Softening annealing treatment: The wire rod obtained by rolling is subjected to softening annealing treatment; (5) Drawing: The softened wire rod is drawn to obtain the low alloy ultra-high strength steel wire for arc additive manufacturing.

3. The method for preparing low-alloy ultra-high-strength steel wire for arc additive manufacturing according to claim 2, characterized in that: In step (1), the vacuum degree of vacuum smelting is 13-18 Pa. The specific parameters for the initial melting and forging of the electrode are: the ingot is held at 1050-1100℃ for a set time to reduce ingot segregation; the forging electrode sample is forged at a final forging temperature of not less than 900℃; the specific parameters for the electroslag remelting process are: electroslag speed 1.4-1.8 kg / min, voltage 26-30V, current 1.6-2.0kA.

4. The method for preparing low-alloy ultra-high-strength steel wire for arc additive manufacturing according to claim 2, characterized in that: In step (2), the specific process of high-temperature forging is as follows: the ingot is held at 1000-1050℃ for a set time, forged into a bar shape, and the final forging temperature is not lower than 900℃, followed by air cooling.

5. The method for preparing low-alloy ultra-high-strength steel wire for arc additive manufacturing according to claim 2, characterized in that: In step (3), the specific process of high-temperature rolling is as follows: the forged bar is kept at 1000-1050℃ for a set time and rolled into wire rod in multiple passes, and then air-cooled.

6. The method for preparing low-alloy ultra-high-strength steel wire for arc additive manufacturing according to claim 2, characterized in that: In step (4), the specific parameters for softening annealing are: keeping the wire rod in a salt bath at 950℃-1050℃ for a set time to reduce the hardness of the wire rod, followed by air cooling.

7. The method for preparing low-alloy ultra-high-strength steel wire for arc additive manufacturing according to claim 2, characterized in that: In step (5), the specific drawing process is as follows: remove the oxide scale from the surface of the wire rod, wash and dry it with water, then perform a film treatment, dry it and then draw it. During the drawing process, perform online annealing at 950-1000℃, and then perform alkaline washing and water washing after annealing.

Citation Information

Patent Citations

  • Equipment and method for manufacturing maraging steel large component through electric arc additive

    CN116460391A

  • High strength steel wire for arc additive manufacturing, and preparation method thereof

    CN110172644A

  • METHOD FOR MANUFACTURING HIGH-TENSILE STEEL FOR LASER BEAM WELDING OR LASER BEAM ARC HYBRID WELDING HAVING TENSILE STRENGTH OF &gt;=1,100 MPa

    JP2011174154A